Acute effects of benzo[e] pyrene in rats - Mazlina Mazlan (2005.)
Malaysia has experienced several episodes of haze with varying degrees of severity. However, no conclusive study was conducted been done to assess the effects of each pollutant on the pulmonary system. Thus, it is the aim of this study to assess the effect of Benzo[e]pyrene on the lungs of rats via intratracheal instillation. Rats were divided into three groups, control, 1 hour post-instillation (p.i.) and 24 hr p.i. The dose of BeP was instilled into the trachea of anaesthetized rats based on the peak haze value during the 1997 episode. Samples of lung lavage were assayed for alveolar macrophage activity (AMO), IgA and IgG while serum level of the mentioned immunoglobulin was also determined. The lung tissue was also taken for histologic examination. The results showed that as time advance, there was marked suppression of AMO and immunglobulins especially that of IgG. Likewise, histologic appearance showed evidence of epithelial hyperplasia, necrosis, inflammation and apoptosis. The amount of fibrinous exudation was very severe in the 1 hr p.i. rats as compared to those at 24 hr p.i. This study proved that BeP can generate lesions in the lung leading to impairment of its immune and defense system.
Project paper (D.V.M.) - Universiti Putra Malaysia, 2005.